EFEKTIFITAS PENGGUNAAN TABLET FE TERHADAP KENAIKAN KADAR HB IBU HAMIL DI PUSKESMAS BINTARA JAYA - wahyuni, Dwi Reza (Politeknik Tiara Bunda, 2023)
One of the causes of iron deficiency anemia is the lack of adequate intake of food sources of Fe and absorption of iron. The results of the 2013-2018 Riskesdas Ministry of Health show that the prevalence of anemia in pregnant women in Indonesia has increased from 31.7% to 48.9% (Riskesdas, 2018). The government targets to reduce this figure to 29% by 2019. This study aims to determine the effectiveness of the use of Fe tablets with the incidence of anemia at the Bintara Jaya Health Center, West Bekasi. This study uses a Quasy experimental study with a Two Group pre-test and post-test design. The population is all pregnant women who have their pregnancy checked at the Bintara Jaya Health Center, West Bekasi. The sample is 50 people using purposive sampling. The statistical test used is the independent sample t test. The results showed that there was an increase in the average Hb level for the group given Fe tablets as much as 0.564, from an average Hb of 10.736 to 11.3. While the increase in the average Hb level for the group that was not given Fe tablets was 0.252, from an average Hb of 10,484 to 10,736. This means that there is a significant difference in the increase in Hb levels of pregnant women both before and after being given Fe tablets. The results of statistical tests showed that there was an effectiveness of giving Fe tablets on Hb levels in pregnant women to prevent anemia with a p value of 0.000 (p < 0.05). The use of Fe tablets is proven to be able to increase the Hb level of pregnant women in preventing anemia. It is expected that pregnant women will enrich their knowledge about anemia and routinely consume Fe tablets and participate in health education programs through various sources.